Validation of a high-throughput and robust technique: BACs-on-beads assay (KaryoLite BoBs) for pre-implantation aneuploidy screening - Grace Wing Shan Kong; Yanlin Ma; Jian Ou; Yvonne Ka Yin Kwok; Wei Wang; Queenie Sum Yee Yeung; Cherry Kit Man Wong; Qi Li; Wen Xu; Weiying Lu; Hong Li; Tin Chiu Li; et al. (Elsevier, 2017)
Objective: This study aims to validate the BACs-on-Beads (BoB) technology as a robust and high throughput method for pre-implantation genetic screening (PGS) for aneuploidy. Material and methods: The performances with respect to the sensitivity, specificity, success rate and detection rate of this technique from new BoBs technology and traditional array chromosomal genomic hybridization (aCGH) were compared. And the use of BoBs as a screening tool for euploid embryos in PGS was evaluated. Result: In the first part of validation study, there were total 75 embryos completed PGS by both BoBs and aCGH. The success rate of PGS was 97.4%, and the results showed 100% concordance between BoBs and aCGH for aneuploidy. In the second part, a total 219 embryos were involved. The success rate of PGS by BoBs was 100%. BoBs identified 28% (62/219) euploidy which were further confirmed to be euploidy by aCGH. Conclusion: This new strategic approach using BoBs as a first tier PGS screening tool and aCGH as a confirmatory tool can increase the throughput of PGS with a reduced cost and time to meet the demand in high volume units.